Dynamic nonrobotic telemicroscopy via skype: A cost effective solution to teleconsultation - Sahussapont J Sirintrapun; Adela Cimic (Elsevier, 2012)
Context: Skype is a peer to peer software application that has been historically used for voice and video calls, instant messaging, and file transfer over the Internet. Few studies are available using Skype specifically for telepathology. Aims: Our aim is to show that dynamic nonrobotic teleconsultation is possible and even effective via means of a standard microscope camera capable of live acquisition, Skype, an established broad band internet connection, and experienced pathologists. Settings and Design: Both the consulting "sending" pathologist and consultant "receiving" pathologist are reasonably experienced general surgical pathologists at junior attending level with several years of experience in sign out. Forty-five cases were chosen encompassing a broad range of surgical pathology specimens. The cases were prospectively evaluated with the consultant diagnosis used as a preliminary pathologic impression with the final diagnosis being confirmation. Materials and Methods: Versions of Skype 5.0 and above were used along with established broadband internet connections, usually between academic medical institutions. Results: Forty of forty-five cases (89%) were essentially concordant. In four of forty-five cases (9%), the consulting impression gave a differential, but favored an entity which did not match the final diagnosis. Only one case (2%) did the consulting impression not match the final diagnosis; a discordant opinion. Conclusions: The image quality via Skype screen sharing option is excellent. Essentially no lag time was seen. We have shown in our small pilot study that Skype is an effective cost-efficient means for teleconsultation, particularly in the setting of entity-related differential diagnoses in surgical pathology and when both the consulting and consultant pathologists are reasonably experienced.